GATOR1 GENE VARIANTS IN FOCAL EPIELPSY - Kovačević, Maša; Novaković, Ivana; Vojvodić, Nikola (Medicinski podmladak, 2023)
Significant genetic contributions to focal epilepsy have only recently been recognized, despite the well-established hereditary nature of other epilepsy syndromes. In 2013 the significant role of DEPDC5 gene in a rare familial focal epilepsy syndrome was described, followed by the discovery of variants in NPRL2 and NPRL3 genes in patients with similar clinical features three years later. The genes listed above code the three subunits that comprise the GTPase-activating protein (GAP) activity towards Rags 1 (GATOR1) complex, a negative regulator of mechanistic target of rapamycin (mTOR) complex 1 (mTORC1). Loss of function of GATOR1 leads to constitutive mTORC1 activation that is linked to various malformations of cortical development (MCD), most notoriously focal cortical dysplasia (FCD), but has also been linked to epilepsy in the absence of overt MCD. Variants in GATOR1 genes have been detected in multiplex families with rare familial focal epilepsy syndromes where they demonstrate an autosomal dominant inheritance pattern with reduced penetrance. More recently, they have also been defined as major contributors in common nonacquired focal epilepsy in which they are detected in 3% of familial and 0.2% of sporadic cases and are particularly common in familial epilepsy associated with FCD where up to 11% of affected subjects carry gene variants. Clinical features of carriers include a propensity for nocturnal seizures, a poor response to antiseizure medication as well as an increased risk of sudden unexpected death in epilepsy, which is why other forms of treatment have been explored, including epilepsy surgery after which GATOR1 gene variant carriers have similar outcomes to other patients with focal epilepsy. A particularly promising avenue of exploration is the utilization of mTOR inhibitors like everolimus in epilepsy treatment, but further investigation into this option is warranted.
Keywords: focal epilepsy, genetic epilepsy, DEPDC5, NPRL2, NPRL3, GATOR1